2020
DOI: 10.1155/2020/6973469
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Nutritional Characteristics in Middle-Aged and Elderly Sarcopenia Patients with Type 2 Diabetes

Abstract: Sarcopenia is considered to be a new complication of type 2 diabetes (T2DM) leading to increased risk of adverse outcome. We performed a survey to evaluate glucose metabolism and nutritional status in sarcopenia patients with T2DM. Diabetic participants aged ≥50 years were grouped into a probable sarcopenia group with low muscle strength ( n = 405 ) and a nonsarcopenia group wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
(17 reference statements)
2
15
0
Order By: Relevance
“…Considering that skeletal muscle plays a major role in glucose metabolism, most previous research concerns the negative relationship of muscle mass with T2D ( 24 26 ). However, a recent study has shown that sarcopenia is a new complication of T2D ( 27 ), and there is a reverse causality between muscle mass and T2D in middle-aged and elderly individuals. In order to exclude the influence of confounding factors such as age and degenerative disease, the study of the pediatric population could be better to clarify the relationship between muscle mass and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that skeletal muscle plays a major role in glucose metabolism, most previous research concerns the negative relationship of muscle mass with T2D ( 24 26 ). However, a recent study has shown that sarcopenia is a new complication of T2D ( 27 ), and there is a reverse causality between muscle mass and T2D in middle-aged and elderly individuals. In order to exclude the influence of confounding factors such as age and degenerative disease, the study of the pediatric population could be better to clarify the relationship between muscle mass and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some articles further explored the aspect of the relationship between malnutrition and sarcopenia. One study evaluated some metabolic characteristics (including parameters of glucose metabolism) in addition to the nutritional status of both middle-aged and elderly subjects with sarcopenia and T2DM [34]. Subjects were grouped into a probable sarcopenia group (low muscle strength, n = 405) and a non-sarcopenia control group (normal muscle strength, n = 720).…”
Section: Recent Evidence About Relationship Between Nutrition Sarcopenia and Diabetesmentioning
confidence: 99%
“…In a multicentre study of 588 Japanese patients with T2DM, it was found that poor glycaemic control was significantly associated with SMM or gait speed in Japanese patients 97 . A recent survey in T2DM patients with or without sarcopenia revealed that sarcopenia patients with T2DM had worse glucose metabolism and nutritional status 98 . Therefore, the importance of nutritional and metabolic control for the prevention of muscle decline and sarcopenia is highlighted.…”
Section: Rational Use Of Anti‐diabetic Drugs To Reduce the Risk Of Sarcopeniamentioning
confidence: 99%
“… 97 A recent survey in T2DM patients with or without sarcopenia revealed that sarcopenia patients with T2DM had worse glucose metabolism and nutritional status. 98 Therefore, the importance of nutritional and metabolic control for the prevention of muscle decline and sarcopenia is highlighted. To decrease the risk of sarcopenia, optimization of nutritional therapy is undoubtedly needed in diabetes care.…”
Section: Rational Use Of Anti‐diabetic Drugs To Reduce the Risk Of Sarcopeniamentioning
confidence: 99%